The Examination of the Relationship Between Experimental Climate and Dimensions of the Creative Organization - Strugar Jelača, Maja; Bjekić, Radmila; Aleksić, Marko; Berber, Nemanja (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
?he subject of the research is reflected in the analysis of the factors of importance for the formation of a creative organization. The paper aims to determine whether or not there is a positive relationship between the experimental climate and the dimensions that describe a creative organization model with a focus on organizational culture. The research hypotheses were generated and empirically analyzed based on a survey conducted on a sample of 145 employees in organizations in the territory of the Republic of Serbia. The survey was developed by combining two methodologies formulated by the authors G. Ekwall, "Creative Climate Model," and T. Amabile, "Organizational Creativity Model." Statistical methods, such as correlation analysis and analysis of variance, ANOVA, were applied in the paper. The obtained results indicate that there is a positive statistically significant relationship between all three dimensions of creative organizational culture, such as flexible management system, motivation for greater achievements and freedom to use resources to form an experimental climate in the organization. Furthermore, by applying ANOVA, it was found that there was a statistically significant difference in the degree of experimental climate prevailing in the organization depending on its size, while no statistically significant difference between the organizations depending on their legal form was confirmed. Finally, the paper highlights management measures to encourage the creation of a creative work environment.